Do Maternal Dietary Antioxidants Modify the Relationship Between Binge Drinking and Small for Gestational Age? Findings from a Longitudinal Cohort Study. (7th September 2018) - Coathup, Victoria; Northstone, Kate; Izadi, Hooshang; Wheeler, Simon; Smith, Lesley
Abstract : Background: Vitamin C, vitamin E, and carotenoids are potent dietary antioxidants that have been shown to attenuate ethanol‐induced harm in animal models of fetal alcohol spectrum disorders. A diet low in antioxidant‐rich foods may induce a state of oxidative stress in the context of maternal alcohol consumption during pregnancy, potentially causing growth restriction in the developing fetus. Methods: We conducted a secondary analysis of a longitudinal U.K. birth cohort. The sample comprised 9, 699 women and their babies in Avon, U.K., with an estimated delivery date between April 1, 1991 and December 31, 1992. Alcohol consumption data were self‐reported at 18 weeks' gestation via a postal questionnaire. Women reported any binge drinking (≥4 U.K. units/occasion) during the past month. Dietary data were self‐reported at 32 weeks' gestation using a food frequency questionnaire. Estimated intakes of vitamins C and E and carotenoids were categorized into quartiles. Logistic regression models with interaction terms were used to investigate relationships between maternal binge drinking, dietary antioxidants, and fetal growth. Models were adjusted for maternal sociodemographic and lifestyle characteristics. Small for gestational age (SGA; <10th percentile) was defined using customized birth centiles. Results: In the unadjusted models, binge drinking was associated with higher risk of SGA birth (odds ratio [OR] 1.38, 95% confidence interval [CI] 1.10, 1.72, p  = 0.005), and higher maternal intakes of vitamin C (OR = 0.90, 95% CI 0.84, 0.96, p  = 0.002) and vitamin E (OR = 0.90, 95% CI 0.84, 0.95, p  < 0.0001) were associated with lower risk of SGA birth. However, addition of potentially confounding variables attenuated these relationships. Likelihood ratio tests indicated that interaction terms were not significant for vitamin C ( p  = 0.116), vitamin E ( p  = 0.059), or carotenoid intakes ( p  = 0.174). Conclusions: There was no evidence of maternal intake of dietary antioxidants modifying the relationship between maternal binge drinking and SGA birth. Abstract : Dietary antioxidants have been shown to attenuate ethanol‐induced harm in animal models of fetal alcohol spectrum disorder. We conducted a secondary analysis of a longitudinal birth cohort to explore whether vitamin C, vitamin E and carotenoids modified the relationship between maternal binge drinking during pregnancy and small for gestational age (SGA). However, we found no evidence of effect modification and associations between binge drinking, dietary antioxidants and SGA were attenuated once potential confounders were added to the model.